A retrospective cohort study of blood hemoglobin levels in blood donors and competitive rowers - Johansson, P. I.; Ullum, H.; Jensen, K.; Secher, N. H. (Scandinavian Journal of Medicine & Science in Sports, 2009)
To investigate the distribution of blood hemoglobin levels in healthy blood donors and elite athletes, a retrospective cohort study from 2001 to 2005 of candidate blood donors and elite rowers in Denmark was performed. Eighty-five thousand eight hundred and forty-six blood donors were identified (36 962 males), and 3.9% of the males had a blood hemoglobin above 10.5 mM, equalling a hematocrit of 51% and, 1.6% of the females had hemoglobin above 9.7 mM, corresponding to a hematocrit above 47%. One thousand four hundred and six rowers (1116 males) were investigated and 10.4% of the males and 8.3% of the females demonstrated values above the recommended limit for athletic competition. Thus, the prevalence of a high hemoglobin value was greater in the rowers, of both gender, than in the candidate blood donors (P<0.0001). The data demonstrate that high hemoglobin levels in blood are seen regularly in normal people and especially in competition athletes.